ROLE OF CALCIUM-REGULATING HORMONES, ADIPOCYTOKINES AND RENAL FUNCTION TEST IN THE PROGRESS OF TYPE 2 DIABETES MELLITUS IN A SAMPLE OF IRAQI PATIENTS - & Al-Lami, Al-Attaby (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A cross-sectional study was conducted on 80 type 2 diabetic patients aged 20-60 years in Baghdad and 20 non diabetic persons as controls. Laboratory assessment of glucose related parameters; Fasting blood sugar (FBS), Glycated hemoglobin (HbA1c), Insulin and Insulin resistance (IR), renal function test; Blood urea, serum creatinine, Calcium (Ca) and Phosphorus (P), Calcium regulating hormones; Parathyroid hormone (PTH), calcitonin and vitamin D, cytokines, Adiponectin and Tumor necrosis factor (TNF-α) and comparison these parameters between patients and controls. The results: a high significant (p˂0.01) increase in FBG level in the patients (211.34 ± 11.20 mg/dl) as compared with control (85.89 ± 3.07 mg/dl). A high significant (p˂0.01) increase in HbA1c in the patients (8.89 ± 0.24 %) than to control (4.813 ± 0.09 %), insulin and HOMA2-I.R levels showed a high significant (P< 0.01) increase of patients as compared to control (49.87 ± 15.78 vs. 12.16 ± 2.57 µIU/ml), (28.49 ± 10.77vs. 2.618 ± 0.56 µIU/ml) respectively. A high significant (P<0.01) increase in B. urea and S. creatinine in the T2DM patients (35.77±1.13 mg/dl and 0.84± 0.04 mg/dl, respectively) and control (30.04±0.69 mg/dl and 0.60±0.03 mg/dl, respectively). The calcium level (8.33±0.06 mg/dl vs. 8.59±0.09 mg/dl) shows a significant (P<0.05) decrease in patients. No significant differences in PTH and calcitonin levels between patients and control, vit. D level, there was a high significant (P<0.01) decrease in patients (16.27 ± 0.55 ng/ml) and control (21.42 ± 2.15 ng/ml). Adiponectin was lower significantly (P<0.05) in patients (11.23 ± 0.40 µg/ml) than in control (12.38 ± 0.61 µg/ml), while there was no significant deference between the patients and control in TNF-α. Conclusion: Development of T2DM characterized by hyperglycemia, hyperinsulinemia accompanied with elevated levels of HbA1c and IR, hyperglycemia is the major cause of progressive renal damge, and the decreased levels of vitamin D in the diabetic patients suggest that altered vitamin D and calcium homeostasis may play role in the development of T2DM.